Molecular phylogenetic relationships of Melanthiaceae (Liliales) based on plastid DNA sequences. (27th April 2016) - Kim, Sang‐Chul; Kim, Jung Sung; Chase, Mark W.; Fay, Michael F.; Kim, Joo‐Hwan
Abstract : Melanthiaceae (Liliales) comprise 17 genera of rhizomatous or bulbous perennials and are distributed across the Northern Hemisphere. The relationships among the five tribes in this family have been evaluated in many molecular and morphological studies. In this study, we performed a phylogenetic analysis of the 17 genera, including 106 species of Melanthiaceae sensu APG III and nine related species as outgroups, based on sequences of five plastid regions ( atpB, rbcL, matK, ndhF and trnL‐F ). Support values for the monophyly of the family (BSMP = 96%, BSML = 100%, PPBI = 1.00) and each tribe were improved in comparison with previous studies. Among the tribes, Melanthieae were sister to the remainder of the family and sister relationships between Xerophylleae and Parideae (BSMP = 96%, BSML = 100%, PPBI = 1.00) and Chionographideae and Heloniadeae (BSMP = 96%, BSML = 100%, PPBI = 1.00) were confirmed. Notably, the generic concept of Veratrum s.l . including Melanthium was not supported in the present study and these genera should be treated as distinct. In the case of Parideae, the relationship of Trillium govanianum to the other species remains uncertain and requires further studies. Finally, we mapped seven representative morphological characters onto the molecular phylogenetic tree for Melanthiaceae.